2011
DOI: 10.1016/j.ijsolstr.2010.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic crushing and energy absorption of regular, irregular and functionally graded cellular structures

Abstract: a b s t r a c tThe in-plane dynamic crushing of two dimensional honeycombs with both regular hexagonal and irregular arrangements was investigated using detailed finite element models. The energy absorption of honeycombs made of a linear elastic-perfectly plastic material with constant and functionally graded density were estimated up to large crushing strains. Our numerical simulations showed three distinct crushing modes for honeycombs with a constant relative density: quasi-static, transition and dynamic. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
116
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 315 publications
(138 citation statements)
references
References 57 publications
7
116
0
1
Order By: Relevance
“…Compared with a uniform foam with equal mass, Cui et al (2009) suggested that a functionally graded foam can exhibit superior energy absorption. Ajdari et al (2011) studied the dynamic crushing of functionally graded cellular structure with regular and irregular cellular arrangements. Results showed that decreasing the relative density along the loading direction enhanced the energy absorption of honeycombs at early stages of crushing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with a uniform foam with equal mass, Cui et al (2009) suggested that a functionally graded foam can exhibit superior energy absorption. Ajdari et al (2011) studied the dynamic crushing of functionally graded cellular structure with regular and irregular cellular arrangements. Results showed that decreasing the relative density along the loading direction enhanced the energy absorption of honeycombs at early stages of crushing.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, in the aforementioned literatures, little detailed analysis focuses on the stress at both the impact and stationary side, moreover, there are some disagrees about the energy absorption of graded cellular structures (Ajdari et al, 2011;Zeng et al, 2010;Fan et al, 2013;Shen et al, 2013). Therefore, it is much necessary to further investigate the dynamic behaviors of graded cellular structures.…”
Section: Introductionmentioning
confidence: 99%
“…They have also analyzed different mechanisms of structure cells deformation and have represented the stress-velocity diagrams. Ajdari et al [10] analyzed the dynamic destruction behavior and the value of energy absorption in regular, irregular and FG honeycomb structures. They studied different modes of deformation and the value of energy absorption in these structures using FEM.…”
Section: Introductionmentioning
confidence: 99%
“…Cui et al (2009) extensively studied the influence in energy absorption capability of foam with five different density gradient profiles under low speed impact loading and concluded that functionally graded foams were better in energy absorption than the uniform foam. Honeycomblike structures with gradient were also theoretically and numerically investigated (Ali et al, 2008;Ajdari et al, 2011). Zeng et al (2010) investigated the influence of the density gradient profile on the mechanical properties of the graded polymeric hollow sphere agglomerates with…”
Section: Introductionmentioning
confidence: 99%